Desarrollo cognitivo en el proceso de enseñanza - aprendizaje de la matemática en los estudiantes de quinto y sexto grado de la Unidad Educativa Intercultural Bilingue " Luis Telmo Paz y MIÑO." - Copara Llumiquinga, Inés Marlene (2021)
This research addressed the topic Cognitive development in the teaching-learning process of Mathematics in fifth and sixth grade students of the Luis Telmo Paz y Miño Intercultural Bilingual Educational Unit, because the cognitive part in students is fundamental because it allows , analyze, reason, solve everyday problems and better understand this subject that has been considered essential for the intellectual development of children, the main objective was to guarantee cognitive development in the teaching-learning process of Mathematics, through the manual developed for the use of didactic materials, the applied methodology had a quantitative approach, which is segmented to a certain group, statistically describing or estimating facts and showing relationships between variables, causality, performance and interrelation, evaluation instruments were applied that made it possible to measure quantifiable data, measurable facts, both at the beginning and at the end of the investigation, surveys that were applied to the students were used, the results obtained after the application of the proposal show the development of skills raised, by 75%, with respect to the initial results that had less than 50%, according to the analysis it is concluded that, to strengthen the cognitive development in the students it was necessary to use didactic materials such as: the Taptana, Base 10 and Tangram, because by manipulating them, it allowed the student to modify their cognitive structure thus facilitating the learning process, finally it is stated that this research work will be very useful because it will help to improve the educational process.